(untitled) (World Bulletin of Management and Law, 2024)
This article explores the necessity of regulating “emojis” within the virtual space from a legal perspective. Emojis have become an integral part of digital communication, widely used across social media platforms and messaging apps to enrich and express textual messages. However, the widespread use of emojis has raised several legal concerns, including issues related to copyright, intellectual property, personal rights, and the potential for harmful or offensive content.